IDENTIFIKASI DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI CIUJUNG DENGAN MODEL WASP DAN STRATEGI PENGENDALIANNYA - Heny Hindriani (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractCrucial Issues at the downstream Ciujung river is the increasing load of water pollution.BOD is one of the water pollution indicator in the stream. This study aimed to determine theamount of Total Maximum Dailly Load (TMDL)in Ciujung River as a basis for determiningriver pollution control strategies. TMDL of BOD determined by modeling WASP (Waterquality Analysis Simulation Program) and the results were compared with the standarstreams due to PP No.82/2001. Water pollution control strategies of Ciujung River determinedby analysis of the results of an expert survey method with AHP (Analytical Hierarchy Process).The results showed that the water quality of Ciujung rivers at minimum reliable dischargemeets the river standard of 4th class along the 13.5 km. Simulation results at maximumreliable discharge and reduction of point source pollution load by 90% indicates that thewater quality in the segment Nagara to Tirtayasa (27.5km) can meet the 4th class of riverquality standard with average TMDL 21,241.74 kg/day. whereas downstream areas, whichdo not meet 4th class of quality standards along 4.5 km. Alternative strategies of Ciujungrivers water pollution control with the aim of reducing the pollution load is tighteninglicensing waste disposal (eigen value 0.260).